The mechanism of the inhibition by carbonic acid of the smooth muscle contraction produced by histamine and oxytocin - Halpern, B. N. (1959)
Carbonic acid inhibited the stimulating action of histamine on guinea-pig intestine and of oxytocin on the uterus of many animal species. This effect was relatively specific. Under the same conditions the actions of acetylcholine, KCl, adrenaline (on rabbit uterus), and ergot alkaloids were not inhibited. The electrical excitability of smooth muscle was similarly not affected. The inhibitory action of carbonic acid is directly proportional to its concentration in the medium in which the isolated organ is maintained. The study of the activity of histamine and oxytocin at different pH in a medium free of NaHCO(3) and buffered with a mixture of sodium maleate and maleic acid suggested that the inhibitory action exerted by carbonic acid was specific and independent of the simultaneous modifications of the hydrogen ion concentration. The mechanism of these phenomena is discussed.